2017
DOI: 10.1016/j.jrras.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficacy of entomopathogenic nematodes by gamma radiation in controlling Spodoptera littoralis larvae

Abstract: a b s t r a c tNowadays, finding a safe control program is the aim of all researchers. The goal of this work is to investigate the effect of gamma radiation on the Entomopathogenic nematodes, Steinernema scapterisci and Heterorhabditis bacteriophora Poinar (HP 88 ) efficacy were tested against larvae of cotton leaf worm, Spodoptera littoralis (Boisd.) under laboratory conditions. Results showed that 2 Gy irradiated S. scapterisci and H. bacteriophora were substantially effective in controlling S. littoralis la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Research on the effect of gamma radiation on entomopathogenic nematodes showed that infective juveniles of Steinernema scapterisci Nguyen and Smart (Steinernema: Steinermatidae) and H. bacteriophora irradiated with 2 Gy gamma radiation were more effective in biocontrol of Egyptian cotton leafworm, Spodoptera littoralis Boisduval (Lepidoptera: Noctuidae), than were nonirradiated nematodes. Similar results were obtained for S. carpocapsae BA2 [169,170].…”
Section: Radiationsupporting
confidence: 87%
See 1 more Smart Citation
“…Research on the effect of gamma radiation on entomopathogenic nematodes showed that infective juveniles of Steinernema scapterisci Nguyen and Smart (Steinernema: Steinermatidae) and H. bacteriophora irradiated with 2 Gy gamma radiation were more effective in biocontrol of Egyptian cotton leafworm, Spodoptera littoralis Boisduval (Lepidoptera: Noctuidae), than were nonirradiated nematodes. Similar results were obtained for S. carpocapsae BA2 [169,170].…”
Section: Radiationsupporting
confidence: 87%
“…Significant deterioration in survival and infectivity [164] Radiation Wavelength of 366 nm No noticeable changes [166,167] Wavelength of 254 nm, with an exposure time of >1.75 min Reduced pathogenicity and reproduction and increased mortality [166,167] Gamma radiation Improved biological effectiveness against plant pests [169,170] Soil aeration 1-20% High survivability and density [164,173] Low oxygen content Significant increase in mortality [171,172] Metal ions Cd(II) and Pb(II)…”
Section: <4mentioning
confidence: 99%
“…Salem et al (2014) concluded that gamma irradiated (2Gy) S. carpocapsae may attribute as a major control method of G. mellonella. Sayed and Shairra (2017) and Sayed et al (2018) stated that 2Gy irradiated S. carpocapsae was more pathogenic than non-irradiated one against S. littoralis larvae. In addition, Sayed et al (2018) suggested that 2 Gy irradiated S. scapterisci can serve as a bio-control method for controlling B. zonata.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Sayed et al (2015) declared that 2 Gy irradiated S. carpocapsae disrupted the antioxidant contents of S. littoralis larvae that led to larval death faster than normal S. carpocapsae. Also, Sayed and Shairra (2017) reported changes in phenoloxidase activity, lysozyme activity, and LDH activity of S. littoralis larvae treated with irradiated and non-irradiated S. scapterisci.…”
Section: Resultsmentioning
confidence: 99%
“…They found that, the efficiency was enhanced against G. mellonella. (Sayed, 2011) and Spodoptera littoralis (Sayed and Shairra, 2017).…”
Section: Discussionmentioning
confidence: 99%